(3x squared-10x)divided by(x-6)=3x+8+48/x-6. but i have no idea how thaproblem was done. pls show me the steps

1 answer

I assume that you mean:

(3x^2 - 10x)/(x-6) = (3x + 8 + 48)/(x-6)

If so, multiply both sides by x - 6.

3x^2 - 10x = 3x + 56

Subtract 3x from both sides.

3x^2 - 13x = 56

Factor out x to give you:

x(3x -13) = 56

x = 56 or

3x - 13 = 56
3x = 69
x = 23

I hope this helps. Thanks for asking.
Similar Questions
  1. Multiple ChoiceWhat is the simplified form of (–3x3y2)(5xy–1)? (1 point) Responses 15 x squared divided by y squared. Image
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 3 answers
more similar questions